THE ROLE OF THE ISLAMIC RELIGIOUS EDUCATION TEACHER IN IMPROVING LEARNING DISCIPLINE ISLAMIC RELIGIOUS EDUCATION SUBJECT DURING THE COVID-19 PANDEMIC AT SMP PLUS AL-ISHLAH BONDOWOSO ACADEMIC YEAR 2020/2021 M. - Agusyanto; Dhalila, Nasifatut (Tsaqofah : Jurnal Pendidikan Islam, 2022)
The Role of PAI Teachers in Improving the Discipline of Learning PAI subjects during the Covid-19 Pandemic at SMP Plus Al-Ishlah in the 2020/2021 academic year. This study uses a qualitative descriptive approach to describe the role of PAI Teachers as Motivators and facilitators in improving the learning discipline of PAI subjects during the Covid-19 pandemic at SMP Plus Al-Ishlah Bondowoso in the 2020/2021 academic year. Data collection techniques using in-depth interview techniques and observation. Then analyzed by reducing data, presenting and concluding the data. (Rahayu, 2011). And it can be concluded that from this research to improve student learning discipline, the important role is the teacher as an educator who provides learning resources and parents who participate in controlling from home.